The Effect of Career Development on Organizational Citizenship Behavior Mediated By Employee Engagement - Ni Kadek Vera Dwi Ocktaviani; Made Surya Putra (Digital Innovation : International Journal of Management, 2025)
This study aims to analyze the effect of career development on organizational citizenship behavior (OCB), mediated by employee engagement, with a case study at Prama Sanur Beach Bali. A saturated sampling technique was used, with the total population of 104 employees serving as the sample. The research method employed was a survey using questionnaires and interviews, analyzed through descriptive statistics and inferential statistical tools using Structural Equation Modeling - Partial Least Squares (SEM-PLS). The results indicate that career development has a positive and significant effect on organizational citizenship behavior. Career development also has a positive and significant effect on employee engagement. Moreover, employee engagement has a positive and significant effect on organizational citizenship behavior and mediates the relationship between career development and organizational citizenship behavior.